2022
DOI: 10.1007/s42322-022-00104-2
|View full text |Cite
|
Sign up to set email alerts
|

Celebrating Diversity and Inclusion in the Outdoors

Abstract: Delegates from 22 countries and four continents assembled in Ireland during September 2019, for the European Institute for Outdoor Adventure Education and Experiential Learning (EOE Network) conference which was themed on the celebration of diversity and inclusion in the outdoors. Conference delegates were invited to have their presentations considered for conversion to journal articles for inclusion in a specially themed issue of JOEE. In this special issue, the majority of articles relate to the inclusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Incorporating culturally diverse and inclusive nature-based activities in the curriculum can ensure that children from different backgrounds benefit equally from outdoor learning experiences. Research has identified the need for greater inclusion and diversity in outdoor experiences; yet, there has been a lack of systematic efforts to transform the mainstream outdoor sector and foster genuine acknowledgment of human cultural diversity [75]. Addressing this lack of diversity in outdoor spaces has the potential to increase the use of and accessibility to nature for families with diverse backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating culturally diverse and inclusive nature-based activities in the curriculum can ensure that children from different backgrounds benefit equally from outdoor learning experiences. Research has identified the need for greater inclusion and diversity in outdoor experiences; yet, there has been a lack of systematic efforts to transform the mainstream outdoor sector and foster genuine acknowledgment of human cultural diversity [75]. Addressing this lack of diversity in outdoor spaces has the potential to increase the use of and accessibility to nature for families with diverse backgrounds.…”
Section: Discussionmentioning
confidence: 99%